STRATEGI PENINGKATAN KINERJA BAPPEDA KABUPATEN MOJOKERTO - hartono, Hartono; yahya, yahya (Majalah Ekonomi, 2017)
Bappeda as a institution which is responsible in course of planning of development area have to synergy and coordinated all element, society element and existing potency in one directional movement, systematic and inwrought. As according to problems focus which have been formulated, hence target of research which will reach is to: 1. identitying strength factor and internal weakness and also threat and opportunity of external influencing performance of BAPPEDA, 2. identifying and formulating strategic issues to face and which must be done by BAPPEDA in order to execution of duty planning of development of area reached by performance in an optimal fashion. This research use secondary data obtaided from on duty or related institution like documents and archives related to target and problems of research. To fulfill the target of research hence used SWOT analysis. This analysis used to analyse qualitative about strength, weakness, threat and opportunity to company. This based of analysis of SAP and ETOP. Then tes litmus to strategic issues, hence obtained four strategy able to be applied to make up of performance of BAPPEDA Mojokerto that is as follows: a. exploit SDM which good to improving professionalism as planner b. develop information system development of district and c. upgrade and quality of product planning of development of area and d. improve, repair planning process and observation of planning of development of area. Key word: SWOT analysis, Autonomous area, Performance